Peak expiratory flow rate of primary school children in high and low air pollution level areas - Ismart Edy Hasibuan; M Nur Supriatmo; A Faisal; Gabriel Panggabean; Ridwan M Daulay; Zakaria Siregar; Helmi M Lubis (Indonesian Pediatric Society Publishing House, 2016)
Background Chronic inhalation of air pollutants may cause bronchoconstriction, bronchiolitis, and edema of airway, thus alter lung volume. To measure the lung volume, a simple lung function test, the peak expiratory flow rate (PEFR), can provide a feature of lung volume in liters/minute. Objective The purpose of this study was to measure PEFR val- ues of primary school children in a high air pollution level area (Medan) and compare the results with the PEFR values of those in a low air pollution level area (Tebing Tinggi). Methods A cross sectional study was conducted on primary school children (10-12 years of age) during May-July 2000 in Medan and Tebing Tinggi. Data were obtained by questionnaires. Physical ex- amination included age, sex, height, weight, and PEFR value. PEFR values were measured by Mini Wright peak expiratory flow meter (MPFM) from three blows. The highest volume was taken as the PEFR value. Statistical analysis was done by t-test and p<0.05 was considered significant. Results There were 212 primary school children eligible for this study; 107 came from the high air pollution level area and 105 from the low air pollution level area. The PEFR values did not dif- fer significantly between the two groups (p>0.05) Conclusion PEFR values in a high air population level area were not statistically different compared with those in low air pollution level area